Enhanced Recovery After Surgery (ERAS) In Patients Undergoing Emergency Laparotomy For Gunshot Injuries At Bacha Khan Medical Complex, Swabi, Pakistan (Journal of Pharmaceutical Negative Results, 2021)
Background: Emergency surgery is essential for life-threatening conditions requiring immediate intervention. The stress response from surgery prolongs recovery, leading to higher mortality rates, hence the need for ERAS protocols.Objectives: This study aims to evaluate the impact of Enhanced Recovery After Surgery (ERAS) protocols on postoperative outcomes in patients undergoing emergency laparotomy for gunshot injuries at BKMC Swabi Pakistan.Study design: A randomized controlled trialDuration and place of study: Department of Surgery, in collaboration with the Department of Anesthesiology from 05-august 2020 to 05-august 2021.Materials and Methods: A randomized controlled trial at BKMC Swabi involved patients aged 18+ with firearm injuries undergoing emergency laparotomy. Patients were randomly assigned to ERAS or conventional care groups. Outcomes measured included length of stay, morbidity, and 30-day mortality, with secondary outcomes of bowel movement time and postoperative complications. Results: It was observed that the LOS of stay in the ERAS group was 4 (1) days whereas in the concurrent care group, this number was 7 (3) days and a statistically significant difference was noticed (p ≤ 0. 001). Likewise, in the conventional care group postoperative complications such as, a chest infection and surgical site infections moderate concerns.